2011
DOI: 10.1016/j.jad.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

What goes up can come down? A preliminary investigation of emotion reactivity and emotion recovery in bipolar disorder

Abstract: Background How is emotion disrupted in bipolar disorder? Two studies are presented that adopt a multi-method approach to investigate emotion reactivity and emotion recovery in bipolar I disorder. Methods Across both studies, individuals with inter-episode bipolar disorder and healthy controls were shown three emotion-eliciting films (neutral, happy, and sad) and experiential and physiological responses were measured. In Study 1, bipolar (BD; n = 23) and non-clinical control (NC; n = 24) participants' emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 49 publications
6
79
4
Order By: Relevance
“…This finding is particularly notable when considered alongside a burgeoning literature suggesting that bipolar disorder is associated with context-insensitive elevations in positive emotion (cf. 34, 35): the type of emotion that people with bipolar disorder are most susceptible to experiencing also confers the greatest vulnerability to their behaving in rash and ill-considered ways. This profile suggests two potential targets for therapeutic intervention in bipolar I disorder: i) developing effective emotion regulation strategies to maintain healthy levels of positive emotion and ii) implementing plans for preventing impulsive behavior when strong positive emotions do unfold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is particularly notable when considered alongside a burgeoning literature suggesting that bipolar disorder is associated with context-insensitive elevations in positive emotion (cf. 34, 35): the type of emotion that people with bipolar disorder are most susceptible to experiencing also confers the greatest vulnerability to their behaving in rash and ill-considered ways. This profile suggests two potential targets for therapeutic intervention in bipolar I disorder: i) developing effective emotion regulation strategies to maintain healthy levels of positive emotion and ii) implementing plans for preventing impulsive behavior when strong positive emotions do unfold.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar disorder has been robustly linked to reward sensitivity (2932) and to intense emotional experiences (33, 34), as well as difficulties regulating emotion (35, 36). Early results from studies in analog samples suggest reward and strong emotion may also represent important preconditions for impulsivity in bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Remitted BD participants were selected to examine more stable patterns of emotional goals independent of current mood (Gruber, Harvey, & Johnson, 2009; Gruber, Harvey & Purcell, 2011). Both BD and CTL participants were recruited from the community using online advertisements and flyers posted in New Haven, CT and surrounding communities.…”
Section: Methodsmentioning
confidence: 99%
“…The cardiac pre-ejection period (PEP), a measure of contractility that reflects beta-adrenergic sympathetic impact on the heart, is a common measure of sympathetic activity (Kelsey, 2012), especially in research on effort and motivational engagement (Obrist, 1976; Silvia et al, 2013). Heart rate variability (HRV) has been used as an index of parasympathetic activity or vagal control, and it has been proposed to be a physiological index of emotional functioning (Gruber et al, 2011; Kogan et al, 2013; Oveis et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Studies of bipolar disorder have variously reported elevated HRV (Gruber et al, 2015, 2011; Kang and Gruber, 2013), decreased HRV and increased LF/HF ratio (proposed to reflect the sympathovagal balance; Chang et al, 2014; Henry et al, 2010; Levy, 2014; Quintana et al, 2016), decreased HRV and decreased LF/HF ratio (Cohen et al, 2003), decreased HRV and no differences in the LF/HF ratio (Moon et al, 2013), and no differences in HRV (Todder et al, 2005). In addition, several studies have found that decreased HRV was associated with severity of mania symptoms (Chang et al, 2014; Henry et al, 2010).…”
Section: Introductionmentioning
confidence: 99%